Design of the Moilme Application for Intelligent Job Recommendations Based on AI and GPS - Laura Monica; Noneng Marthiawati; Kevin Kurniawansyah; Hetty Rohayani; Hafiz Nugraha (Asosiasi Riset Teknik Elektro dan Infomatika Indonesia, 2026)
The increasing tax burden each year poses a significant challenge, particularly for people with limited education and job seekers who struggle to find suitable employment, as most job openings prioritize bachelor's degree holders with work experience, while even graduates often face difficulties since companies typically require prior experience as a primary qualification; as a result, many graduates choose to start their own businesses, which in turn require employees to support their operations. This condition highlights the need for an intelligent solution that connects job seekers—including graduates and those without work experience—with vacancies matching their qualifications. To address this issue, this study designs the Moilme application, which integrates AI-based job matching through Google's Talent Solution API and GPS technology to generate intelligent job recommendations based on job seekers' qualifications while also displaying nearby job locations, with the Black Box method applied to simplify the development process and improve system performance in delivering relevant recommendations. The results show that the designed application successfully provides intelligent job recommendations matching users' qualifications and displays nearby job locations, thereby helping accelerate the job search process for job seekers as well as recruitment for companies and SMEs. The novelty of this research lies in combining AI-based qualification matching with GPS-based location intelligence within a single application, offering smarter and more personalized job suggestions. It is concluded that Moilme has the potential to expand job opportunities for those in need of work while helping companies and SMEs find suitable employees quickly and efficiently.